VEHICLE ROUTING PROBLEM DENGAN APLIKASI METODE NEAREST NEIGHBOR - Prasetyo, Waluyo; Tamyiz, Muchammad (Journal of Research and Technology, 2017)
Transportation problem is just like inventory, this is an activity in logistics area. This activity is possible to make some production in one place and to consume them in another place. The aim of this research were to evaluate the existing network distribution model performance and to provide sugestions to proper the network distribution model used. The applied metode to achieve the goal was Nearest Neighbor Algorithm. The results were: (a) Distance saving was 538,2 Km or 26,59%, (b) Distribution time of product could be reduced to 9,37 hours or 19,07%, (c) Fuel cost could be reduced to 403.650 rupiahs or 26,59%, (d) Driver and assistance cost could be saved to 272.850 rupiahs or 4,5%, and (f) Total of distribution cost could be saved to 676.500 rupiahs or 25,71%.